Perceptions of Journal Quality. - Benjamin, James J.; Brenner, Vincent C.; Strawser, Robert H. (The Accounting Review, 1974)
The article informs that the primary purpose of this study is to determine the subjective evaluations of both department heads and faculty members concerning the quality of selected journals. This is of value since the perceived quality of the journal is apparently an important factor in evaluating an article. In addition, it is also meaningful to compare the department heads' perceptions with the perceptions of the faculty members. Thus, another purpose of this study is to determine if any significant differences exist between department heads' and faculty members' perceptions of the quality of these journals. Data were obtained from a questionnaire sent to a random sample of 200 accounting faculty members and the department heads of the 163 schools of business accredited by the American Association of Collegiate Schools of Business. The questionnaire was divided into two sections. The first section provided a listing of 24 accounting and business related journals. The respondent was asked to evaluate the quality of each journal.